Stephen Sykes: Koinonia, Conflict and Conciliarity - Sagovsky, Nicholas (Ecclesiology, 2019)
Stephen Sykes thought that an overuse of koinonia language pointed to doctrinal fudge. His desire for clarity in the Church's doctrine led him to emphasise the place that conflict plays in the life of the Church. His concern with the failure of Anglicanism to address the tensions within it led him to reflect on the exercise of authority and the deployment of power within Anglicanism. In the Orthodox and Roman Catholic traditions, koinonia is primarily a way of speaking about the life of the Holy Trinity and of participation in the Trinitarian life of God. It cannot then imply or contain conflict. Over thirty years, Sykes came to use koinonia confidently as a way of speaking about the conflicted outworking of authority within the Anglican Communion. He modelled a conciliar magisterium' - a magisterium that is embedded in synodality, that listens to many voices, but affirms episcopacy, and is prepared to teach. Whether such teaching is received can only be seen in the ongoing conciliar process which is the life of the Church.